Pancreatic Mass Leading to Left-Sided Portal Hypertension, Causing Bleeding from Isolated Gastric Varices - Helga Thrainsdottir; Vigdis Petursdottir; Sigurdur Blöndal; Einar S. Björnsson (Case Reports in Gastrointestinal Medicine)
Mucinous cystic neoplasms (MCN) are an uncommon form of exocrine neoplasms of the pancreas. Symptoms are most often vague and this makes the diagnosis more difficult. The current case is one of three cases yet reported where the MCN caused left-sided portal hypertension leading to the formation of isolated gastric varices and subsequent bleeding from the varices. In the previously reported cases the main symptom was hematemesis. However in the current case the patient experienced no hematemesis, only isolated incidents of dark coloured diarrhea, but the main symptoms were those of iron-deficiency anemia. We present the case report of a 34-year-old woman who presented with dizziness and lethargy and was found to have 12 cm MCN in the pancreas.